Manipulation of splitting, sunburn and enhancing coloration of Wonderful pomegranates by preharvest foliar applications - Attia, Said M. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
In order to manipulate splitting, sunburn and enhancing coloration of pomegranates. (Punica granatum L.) cultivar “Wonderful” was treated with Gibberelic acid (GA3) at 20 ppm (w/ v), Calcium Chloride (CaCl2) at 0.5 % (w/ v), ProTone (Active ingredient, Abscisic acid (ABA 10 %) at 100 ppm (v/ v), GA3 plus CaCl2, GA3 followed by ProTone and GA3 plus CaCl2 followed by ProTone. The application of GA3 and CaCl2 treatments were sprayed twice during both years of study (in the second week of May and repeated 30 days after the first spray), in addition to each of the above treatments followed by ProTone at 100 ppm as a coloration treatment, which was sprayed at color initiation on 25, 28 August during 2014 and 2015 respectively. The results indicated that GA3 treatments significantly increased shoot length, fruit length, fruit weight, aril weight and fruit acidity. While, reduced fruit splitting, fruit sunburn, light intensity and peel anthocyanin contents compared with the control treatment. Furthermore, application of 0.5 % CaCl2 significantly increased fruit length, slightly fruit weight, aril weight and fruit acidity. While, reduced fruit splitting as compared with untreated fruits. ProTone treatments at 100 ppm had no effect on physical characteristics but increased peel anthocyanin contents, Total Soluble Solids (TSS), total sugar and reduced fruit acidity of pomegranate fruits. In general, the formulation containing GA3 plus CaCl2 followed by the application of ProTone at 100 ppm proved to be the best for improving vegetative growth, reducing splitting, sunburn and enhancing coloration of pomegranates